HUBUNGAN MAYA INDEX DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI KELURAHAN TEGALSARI KOTA TEGAL - Novia Rokhmawanti; Martini Martini; Praba Ginanadjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Tegalsari Urban Village was one of the endemic areas with the highest dengue cases in Tegal city. Maya index was an indicator to determine high-risk areas as nurseries for larvae by using hygiene risk indicator (HRI) and breeding risk indicator (BRI). The goal of this research was to know the relationship of maya index with dengue hemorrhagic fever incident in Tegalsari Urban Village. This research used observational analitic with cross sectional design. Samples taken as many as 100 homes using purposive sampling method. Measurement of the maya index variables using observation sheet. Data were analyzed using the chi-square. The results of this study indicated that there was a relationship between the maya index with incidence of DHF. The level of risk a high of maya index to the middle of maya index equal to 9 times (POR 9; 95 % CI 1,846-44,082) and the high of maya index to the low of maya index equal to 8,8 or close to 9 (POR 8,8; 95 % CI 1.046 to 74.042).The low of maya index were 21 (21%) homes, middle of maya index were 43 (43 %) homes, and the high of maya index were 36 (36 %). The density of larvae seen of the entomology index in Tegalsari obtained house index (HI) of 66 %, container index (CI) of 16.3 %, and breteau index (BI) of 101 who showed that Tegalsari was an area of high risk of dengue transmission. The suggestion for the health department to train women larva monitoring (Bumantik) with the inspection techniques larvae material either in a controlled (controllable sites) or uncontrolled (disposable sites).